Benzeção, saberes e re-existência do povo indígena Chiquitano no espaço urbano de Porto Esperidião - MT - Silva, Elidiane Martins de Brito (2024)
This work is anchored in the thesis that the traditional art of blessing opens a space for the production of care-healing, knowledge, non-school education and re-existences of the Chiquitano indigenous people in the urban space of Porto Esperidião (MT) going against colonial/capitalist precepts. This is the result of a scientific research carried out with selfdeclared male and female healers of the Chiquitano ethnic group who manage to eke out a living in the urban context of the aforementioned municipality, located in the southwest of the State of Mato Grosso (Brazil). This investigative proposal is connected to studies and discussions carried out by the Study and Research Group on Work and Education (GEPTE) which follows the research line “Social Movements, Politics, and Popular Education” linked to the Postgraduate Program in Education (PPGE) from the Institute of Education (IE) of the Federal University of Mato Grosso (UFMT). The research aimed to analyze the knowledge and educational practices that are mobilized through blessing, in order to understand the dimensions of human life that interweave in work, education, culture and the re-existence of those people who give blessings, in the light of scientific/colonial epistemological beliefs. This participatory research (Brandão, 1983; 1986a; 1986b; 2008; 2012; 2014) had the theoretical framework of the field of dialectical and historical materialism (Kosik, 1976; Frigotto, 1989; Saviani, 2007; Marx, 1980, 2004; Marx and Engels, 1998, 2007) as a basis and a method. The empirical data were gathered from social mapping of Chiquitano male and female healers, semi-structured interviews (with male and female healers and people blessed), observations in blessing sessions and training workshops led by male and female indigenous healers at the school about the traditional art of blessing and the preparation of home remedies. The key finding is that blessing is a work that diverges from the capitalist perspective because it produces value-in-use manifested in care-healing practices which comprehend other ways of teaching, learning, caring, and mediating healing through dialogue with other human beings, with non-humans, with nature, with religion, and with culture. These are authentic and insurgent ways of opening breaches in Western capitalist knowledge that unfortunately plays a dominant role over traditional knowledge.